AB0196 Increased Plasma Soluble Urokinase Plasminogen Activator Receptor Level in Systemic Sclerosis with Impaired Microvascular Abnormalities and Fibrosis. (9th June 2015) - Balog, A.; Legány, N.; Toldi, G.; Distler, J.H.; Beyer, C.; Szalay, B.; Kovács, L.; Vásárhelyi, B.
Abstract : Objectives: Urokinase-type plasminogen activator receptor (uPAR) is a key component of the fibrinolytic system involved in extracellular matrix remodeling and angiogenesis. Novel animal models supported the key role of uPAR not only in fibrosis but also in systemic sclerosis (SSc)-related microvascular abnormalities. The aim of this study was to investigate plasma soluble uPAR (suPAR) levels in SSc, and their association with organ specific progression. Methods: suPAR concentrations were measured by ELISA in SSc patient (n=83) and in healthy controls (n=29). Simultaneously, CRP and ESR were assessed. Detailed clinical data including skin, lung, heart and microvascular characteristics were evaluated at sampling. Results: suPAR values were higher in SSc patients than in controls. Subgroup analysis showed higher suPAR values in diffuse cutaneous- than in limited cutaneous SSc and correlated with anti-Scl-70+. suPAR levels also associated with pulmonary function test parameters of fibrosis, presence of microvascular lesions (e.g. Raynaud phenomenon, naifold capillaroscopic abnormalities and digital ulcers) and arthritis. Conclusions: Our data indicate that suPAR might be a valuable early diagnostic marker of SSc which also correlates with disease severity and progression. Disclosure of Interest: None declared